Organisational innovation facilitators as drivers for international trade between China and European Union - Sousa, M.; Martins, J. M.; Martins, J.M.; Miguel Sousa (Transnational Corporations Review, 2019)
This paper analyses the role of innovation policy and the main facilitators to promote China's international trade in the European Union. The theme Innovation Policy of China to potentiate their international trade in the European Union (EU), from 2014 to 2019. To undertake this, research was established the literature survey. The results show that regarding the research areas there is a multiplicity of themes, including Trade Policy, Digital Trade, International negotiations, Multilateral relations, Leadership, China–Politics & Government, Digital Trade Apps, International Trade, Trade Balance, and Goods balance. Also, the US–China trade war has consequences on the GTC because China, but also the EU and other countries are focussing their trade interest in other regions, especially consumers in Asia, Eurasia, Africa, and South America. For future studies, it is suggested to expand the search for articles concerning China and EU Trade on other databases.